1994
DOI: 10.1097/00007632-199405310-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Pes Cavus and Idiopathic Scoliosis

Abstract: There was a significant correlation between scoliosis and pes cavus--spina bifida was not an etiologic factor. Therefore, in certain patients where scoliosis and pes cavus present jointly, deformity may be secondary to altered balance or to disorders of the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Carpintero et al 25) on the other hand, showed that majority of AIS patients had pes cavus with a prevalence of 65.38% of the 138 AIS patients examined. Interestingly, the incidence of the pes cavus did not relate to the severity and location of the scoliotic curves 25) .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Carpintero et al 25) on the other hand, showed that majority of AIS patients had pes cavus with a prevalence of 65.38% of the 138 AIS patients examined. Interestingly, the incidence of the pes cavus did not relate to the severity and location of the scoliotic curves 25) .…”
Section: Resultsmentioning
confidence: 98%
“…Concerning structural scoliosis and how it relates to lower extremity biomechanics: Apart from apparent leg length discrepancy, AIS has been found to be associated with several lower extremity biomechanics abnormalities [4][5][6] including pes valgus 4) , pes cavus 25) , internal leg rotation 4) , increased femoral shaft angle 26) , increase femoral anteversion/tibial torsion ratio 5) and contractures of hip abductors 27) .…”
Section: Resultsmentioning
confidence: 99%
“…The study of Cole (1983) indicated several forms of claw foot, with specific anatomical features and different outcomes. This deformity is often associated with scoliosis and it may be secondary to altered balance or to disorders of the central nervous system, as shown by Carpintero et al (1994). In a multidisciplinary study of Tynan et al (1992), it was found that in the majority of cases of claw foot, the peroneal compartment was enlarged in relation to the anterior compartment when compared to the normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Having in mind this observation many authors studied the relationship between foot morphology (especially pes cavus) and scoliosis, as it is thought these pathologic conditions may share a common origin. All of them pointed out that there is such a relationship and also that patients with scoliosis are more likely to have cavus foot than the people without scoliosis [57]. The authors investigated whether there is such a relationship in a large Greek children population derived from the SSS program.…”
Section: Is and Cavus Foot Studies In School Screening Referralsmentioning
confidence: 99%